“Radical Moves: Caribbean Migrants and the Politics of Race in the Jazz Age”, de Lara Putnam. - Boza Villarreal, Alejandra (Universidad de Costa Rica, 2014)
Reseña del libro Radical Moves: Caribbean Migrants and the Politics of Race in the Jazz Age, de Lara Putnam.